Evaluating the effectiveness of tele pharmacy services on patient outcomes - Saharan, Priyanka; Srinivasa Rao, Varri (Journal of Neonatal Surgery, 2025)
Pharmaceutical care has caused pharmacy practice to become more patient-oriented rather than medication product-oriented, with the goal of achieving specific results that enhance patients' quality of life. Pharmacists can play a significant role in providing patients with individualized care and specifically in effectively controlling the rising prevalence of chronic non-communicable diseases (NCDs) since patients contact them more frequently. In India, the lack of professional training and ongoing pharmacy education, clinical knowledge, and clinical skills results in low self-esteem and negatively impacts patient care delivery. Community pharmacists must improve their knowledge by learning new things on a regular basis, honing their abilities, and shifting their focus from only distributing medications to more patient-focused services. The community's adoption of efficient pharmaceutical care procedures is hampered by numerous obstacles, which must be found and removed through methodical investigation. The number of elderly people is growing globally. Geriatric health issues demand particular attention because elderly individuals deal with a variety of issues, such as health, social support, and financial instability. An occurrence or circumstance involving drug therapy that fundamentally or hypothetically impedes the patient's expected health outcomes is referred to as a drug-related problem (DRP). The third or fourth most common cause of death for older adults is DRP. The study's objective was to assess how well a pharmacological care program affected the health outcomes of elderly people. The current investigation was a three-year prospective interventional study that was conducted in three stages: preintervention, intervention, and postintervention. Pre-rounds, ward rounds with physicians, and inpatient case records were used to gather information about the patients' medication therapy.